Perianal Paget's disease as spread from non‐invasive colorectal adenomas. Issue 2 (23rd September 2020) - Hutchings, Danielle; Windon, Annika; Assarzadegan, Naziheh; Salimian, Kevan J; Voltaggio, Lysandra; Montgomery, Elizabeth A
Abstract : Aims: Paget's disease of the perianal skin is a rare form of extramammary Paget's disease, and may be a primary intraepithelial adnexal neoplasm or secondary due to spread from an underlying colorectal lesion, nearly always colorectal adenocarcinoma. Secondary perianal Paget's disease associated with non‐invasive colorectal adenomas is exceedingly uncommon, with only a few reported cases. Methods and results: Herein, we present the clinical and pathological features of the largest series of secondary perianal Paget's disease arising in association with colorectal adenomas. There was gender parity and the median age was 72 years (range = 68–76 years). In all cases, perianal Paget's disease was associated with colorectal adenomas, including three (75%) conventional tubular adenomas and one (25%) tubulovillous adenoma with serrated foci. All adenomas had high‐grade dysplasia and one had intramucosal adenocarcinoma (lamina propria invasion; Tis), but all lacked submucosal invasion. The intraepithelial Paget's cells showed a colorectal phenotype by immunohistochemistry in all cases. At follow‐up, two patients had no evidence of disease at 6 and 87 months, one had residual perianal Paget's disease at 8 months and one developed invasive adenocarcinoma of the perianal tissue at 36 months. Conclusions: Similar to its mammary analogue, secondary perianal Paget's disease may arise in association with invasive and/or in‐situ colorectal lesions. Although the latter is an uncommon presentation of a recognised rare disease, knowledge of this phenomenon is important to forestall overdiagnosis of invasion and potential overtreatment. The clinical course is variable, such that close follow‐up is required.